Densification of Y2O3 by flash sintering under an AC electric field. Issue 2 (February 2022) - Nambu, Kohta; Morita, Koji; Soga, Kohei; Yamamoto, Takahisa; Masuda, Hiroshi; Yoshida, Hidehiro
Highlights: Dependence of the AC-flash sintering behavior on frequency was systematically investigated in Y2 O3 . A fully densified Y2 O3 body was successfully obtained by the AC-flash sintering at 1 kHz. The full densification resulted from the high input power at the high onset temperature. Temperature dependence of the power dissipation was influenced by the frequency. The dependence on the frequency was ascribed to the fluctuation of the specimen temperature and phase shift. Abstract: Frequency dependence of the densification behavior of undoped Y2 O3 sintered by the AC-flash sintering was systematically investigated at 500 V·cm −1 over a frequency range from 0.05 Hz to 1 kHz. The Y2 O3 bodies sintered under an AC field showed a uniform microstructure, without an asymmetric grain size distribution between the electrodes. Almost fully-densified Y2 O3 body was consolidated at 1 kHz exhibited a relative density greater than 99 % and an average grain size of 1.6 μm. The almost full densification probably resulted from the high input power at the relatively high onset temperature of 1300 °C at this frequency. The temperature dependence of the power dissipation during the AC-flash sintering experiments can be ascribed to the periodic fluctuations of the specimen temperature at low frequencies and to the phase shift between the applied field and the specimen current at high frequencies.